Plant extract-based nanoemulsion for controlling sweet potato pests and weeds - J. Pumnuan; Anusart Ruddit; Anuwat Lakyat; Thanaporn Doungnapa; Jantra Deemak; Muanfan Thongbang; Suriyasit Somnuek; Naphat Somala; Somsak Kramchote (Scientific Reports, 2025)
The sweet potato weevil (Cylas formicarius) is the most destructive pest of sweet potato and is often associated with diseases and weeds. The use of plant extracts as pest control agents is a promising, eco-friendly approach, but their effectiveness often declines under field conditions. Therefore, nanoemulsion technology was applied to improve the dispersion and bioefficacy of active compounds. In this study, we aimed to develop plant extract-based nanoemulsions as multifunctional biopesticides capable of controlling insect pests, fungal pathogens, and weeds. Twenty-one plant extracts were screened for their effects adult SPW via contact methods. The most potent extracts were then formulated into nanoemulsions and evaluated for insecticidal efficacy—including contact toxicity, repellency, and oviposition inhibition. In addition to insecticidal effects, antifungal and herbicidal activities were systematically assessed against Fusarium sp. and two common weed species in sweet potato fields, Amaranthus tricolor and Echinochloa crus-galli. The major chemical constituents of key extracts were identified using gas chromatography–mass spectrometry (GC–MS). Among all extracts, the hexane extracts of star anise and long pepper exhibited the highest contact toxicity, with LC50 values ranging from 2.051 to 2.415% at 24 h. When formulated into nanoemulsions (NHEF-1 and NHEH-2), toxicity increased 16- to 18-fold, lowering LC50 values to 0.114–0.150%, and at above 0.1%, oviposition was inhibited by more than 85%. Both formulations also demonstrated significant antifungal activity against Fusarium sp. (44.6–56.8% growth inhibition) and completely inhibited the germination of A. tricolor (at 0.01%) and E. crus-galli (at 1.0%). GC–MS analysis revealed anethole (84.49%) as the predominant compound in the star anise extract, with long pepper extract containing moderate amounts of several compounds. These findings demonstrate the potential of plant extract-based nanoemulsions as eco-friendly, multifunctional biopesticides for sustainable sweet potato management, integrating enhanced insecticidal, antifungal, and herbicidal effects.
Keywords: Insect Pest Control Strategies; Nanocomposite Films for Food Packaging; Polymer-Based Agricultural Enhancements